POLITICAL ARCHITECTURE AND LEGAL FRAMEWORK RELATED TO SOCIAL HEALTH PROTECTION SCHEMES IN PAKISTAN: QUALITATIVE INQUIRY OF POLICY MAKERS’ VIEWPOINT - Khan, Sheraz Ahmad; Ayub, Ayaz; Khan, Kashif Ahmad; Khan, Raheel Shahab; Shahzad, Jawad Ahmad; Jamil, Ayisha (Journal of Ayub Medical College Abbottabad, 2018)
Background: Pakistan is a federal state with three tiers of government. Following contentious general elections in 2013, ever first democratic transition took place in Pakistan. Subsequently, two social health protection schemes were launched. Current paper’s objective is to understand the political context in which these schemes were launched and to explore the constitutional position of access to healthcare in Pakistan. This paper also explores the legal protection/ sustainability with regards to these schemes. Methods: We used qualitative research techniques with interpretivist paradigm and case-study approach. In-depth interviews were conducted, followed by content analysis. Triangulation and data saturation were observed to guide our sample size. Officials involved with these schemes at policy and implementation level were interviewed. Ethical approval was taken from ethics board of Khyber Medical University. Based on purposive sampling, in-depth interviews were conducted and thematic analysis was performed. Results: We identified two themes in response to question-1 of our interview, asking about the cause of action behind starting these schemes and their legal protection. These themes were: (i) [initiation of] Social Health Protection as democratization of healthcare, and (ii) [initiation of] Social health protection in legal void. Implicitly, these schemes are a product of grass root political activism and health found berth in election manifestos recently. Also, we deduce that health is not a constitutional right in Pakistan. These schemes lack constitutional guarantee and ensued in absence of overarching legal framework. Conclusion: These social health protection schemes are high on political agenda but lack constitutional and legal protection. Keywords: Universal Health Coverage (UHC); Sustainable Development Goals (SDGs); healthcare financing; health insurance; social health protection; Sehat Sahulat; Prime Minister National health program